Réécriture d’un héritage essentiel: Réflexions sur la notion de « l’aventure » dans la trilogie picaresque de Lesage - Orbázi, Melinda (Verbum – Analecta Neolatina, 2024)
In our contribution, we attempt to examine more closely the role of “adventure” in three novels by Alain-René Lesage, described as picaresque: The History of Gil Blas de Santillane, The Bachelor of Salamanca and The History of Estévanille Gonzalez. Our method is based on microphilological research: after giving a brief historical overview of the expression, we will see the occurrence of “adventure” in the novels, while considering the contexts in which this expression appears and which lead us to some remarks related to the narration. The results of the reflections traced above help us to better orient ourselves in the complex labyrinth of the concept of adventure in the French picaresque novel.